A meta-analysis of the criterion-related validity of Session-RPE scales in adolescent athletes - Liu, H.; Yang, W.; Liu, H.; Bao, D.; Cui, Y.; Ho, M. K.; Li, Q. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background The objective of this study was to establish the criterion-related validity of the session-rating of perceived exertion (s-RPE) method in adolescent athletes.